First postnatal lactate blood levels on day 1 and outcome of preterm infants with gestational age <29 weeks - Zipf, Stephanie; Fortmann, Ingmar; Härtel, Christoph; Andres, Oliver; Frieauff, Eric; Paul, Pia; Häfke, Anna; Reutter, Heiko; Morhart, Patrick; Weller, Ursula; Welp, Amrei; Kipke, Henry; et al. (Frontiers in Pediatrics, 2024)
Background Serum lactate levels are used as biomarkers for perinatal asphyxia, while their value for outcome prediction in preterm infants is uncertain. It was the aim of this observational study to determine the association of the first postnatal serum-lactate levels on day 1 of life and short-term outcome in preterm infants less than 29 gestational weeks. Methods We analysed data in a population-based cohort of German Neonatal Network (GNN) preterm infants with available first postnatal lactate levels enrolled at 22-28 weeks of gestational age (GA) between 1st of April 2009 and 31st December 2020. We hypothesized that high lactate levels as measured in mmol/L increase the risk of intraventricular haemorrhage (IVH) and bronchopulmonary dysplasia (BPD) in infants with VLBW regardless of small-for-gestational-age (SGA) status. Hypotheses were evaluated in univariate analyses and multiple logistic regression models. Results First postnatal lactate levels were available in 2499 infants. The study population had a median GA of 26.7 [IQR 25.2 – 27.9] weeks and birth weight of 840g [IQR 665 – 995]. Infants with short-term complications such as IVH and BPD had higher initial lactate levels than non-affected infants. The positive predictive value of a lactate cut-off 4 mmol/L was 0.28 for IVH and 0.30 for BPD. After adjustment for known confounding variables, each 1 mmol/L increase of day 1 lactate levels was associated with a modestly increased risk of IVH (OR 1.18 95% CI 1.03–1.37; p =0.002) and BPD (OR 1.23 95% CI 1.06–1.43; p =0.005) but not with sepsis or mortality. Notably, SGA was associated with lower risk of any grade and severe IVH (OR 0.70; 95% CI 0.54–0.85; p =0.001). Conclusions In our observational cohort study higher initial lactate levels were associated with adverse outcome regardless of SGA status. However, the predictive value of lactate cut-off levels such as 4 mmol/L is low.